A Nondestructive Method for Estimation of Leaf Area in Quercus aegilops L. Tree - Halmat Sabr (Al-Qadisiyah Journal For Agriculture Sciences)
Non-destructive techniques for leaf area estimation are much sought after by both forest managers and researchers in the fields of biology and forest ecology. Leaf area (LA) can be determined by developing linear metrics, such as leaf length (L) and width (W). The objective of this study was to create a reliable approach for accurately estimating the leaf area (LA) of Quercus aegilops L. by using data of leaf length, width, or other dimensions. Seven non-destructive models were formulated to accurately estimate the leaf area (LA) of the species under investigation, developing the leaf dimensions of length (L) and width (W). The regression models that utilized a single dimension, such as length or breadth, were shown to be less effective in predicting the leaf area of Q. aegilops L. compared to models that integrated the product of length and width measurements. Among the seven produced models, the equation LA = 0.3256L*W1.016 was chosen as the final equation since it was considered the most suitable among the other equations.